Answer:
6.1555
Step-by-step explanation:
the 5 is infinite in 6.15 such as 6.155555555 it does not stop
Answer:
6x² + 5x - 2 = 0
Step-by-step explanation:
Given
2x² - 5x - 6 = 0 ← in standard form
with a = 2, b = - 5, c = - 6, then
sum of roots α + β = -
= ![\frac{5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7D)
product of roots =
= - 3, then
sum of new roots =
+ ![\frac{1}{\beta }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Cbeta%20%7D)
= ![\frac{\beta+\alpha }{\alpha \beta }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cbeta%2B%5Calpha%20%20%7D%7B%5Calpha%20%5Cbeta%20%7D)
=
= - ![\frac{5}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B6%7D)
product of new roots =
× ![\frac{1}{\beta }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Cbeta%20%7D)
=
= - ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
Hence the required equation is
x² +
x -
= 0 or
6x² + 5x - 2 = 0 ( multiplying through by 6 )
Answer:
Please see the attached pictures for full solution.
Answer:
c 2:1
Step-by-step explanation:
If you simplify 14:7 it is 2:1 (divide by 7)
Answer:
B
Step-by-step explanation:
the area of triangle A is k times the area of triangle b